Differentiated approach to rhythm conversion in patients with atrial fibrillation and flutter - A. G. Pronin; A. V. Prokopenko; D. K. Glukhov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The importance of relieving paroxysms of fibrillation and atrial flutter is determined by a huge number of patients suffering from this pathology and its recurrent course.Objective: To create an algorithm for the treatment of patients with atrial fibrillation and atrial flutter by comparing the efficacy and safety of drug-induced rhythm conversion with amiodarone, propafenone, procainamide, niferidil and electropulse therapy.Material and methods. Heart rate conversion was performed in 299 patients. Amiodarone was used as a drug for therapy in 93 patients, propafenone in 34, procainamide in 52, and niferidil in 50. 70 patients underwent electropulse therapy. A comparative analysis was carried out to establish the effectiveness and safety of heart rate conversion by these methods.Results. The effectiveness of conversion rhythm in atrial fibrillation with the help of electropulse therapy, propafenone, niferidil, procainamide and amiadarone has been established, which is 90,3%, 82,4%, 77,4%, 72,5% and 70.5%, respectively. It was also found that the use of electro-pulse therapy and niferidil, in which sinus rhythm recovery occurs in 94.4% and 78.9%, respectively, against 58.3% and 26.7% of patients receiving procainamide and amiodarone, respectively, is most appropriate for the relief of atrial flutter. Often, when using niferidil, ventricular extrasystole and prolongation of the QT interval during electrography developed in comparison with patients of other groups. Ventricular tachycardia, including the "pirouette" type, sinoatrial blockade, AV blockade of various degrees, were also slightly more often registered in these patients.Conclusions. In order to stop atrial fibrillation, there are no differences between medications, and it is better to perform rhythm conversion with atrial flutter with niferidil or electro-pulse therapy.